Analysis of the Use of the Cooperative Integrated Reading and Composition (CIRC) Method in Improving Elementary School Students' English Reading and Writing Skills - Dewinna, Riecha Fizha (International Journal of Curriculum Development, Teaching and Learning Innovation, 2025)
This research focused on evaluating the effectiveness of the Cooperative Integrated Reading and Composition (CIRC) method in improving English reading and writing skills among elementary school students at SDN 194 Sukajadi, Bandung. The study employed a quasi-experimental design, comparing the performance of students exposed to CIRC with those taught using traditional methods. Data was collected through pre- and post-tests measuring reading comprehension and writing proficiency. Results indicated significant improvements in reading and writing skills among students using CIRC, attributed to increased student engagement, active collaboration, and peer interactions. The CIRC method proved particularly effective in fostering critical thinking, enhancing reading comprehension, and promoting organized writing. These findings suggest that CIRC can be an effective instructional approach for enhancing language skills in elementary education, offering valuable insights for educators seeking to improve language learning outcomes.